Thioredoxin-1 promotes the restoration of alveolar bone in periodontitis with diabetes - Jinyan Wu; Yaxian Huang; Chi Zhan; Lingling Chen; Zhengmei Lin; Zhi Song (iScience, 2023)
Summary: Treatment of periodontitis in people with diabetes remains challenging. The present study aimed to investigate the therapeutic potential of thioredoxin-1 (TRX1) in periodontitis with diabetes, as well as its role in modulating osteogenic differentiation. Our findings indicated that the production of reactive oxygen species (ROS) was elevated, while the expression of TRX1 was significantly reduced in the periodontal tissues of periodontitis mice with diabetes. Furthermore, knockdown of TRX1 in periodontal ligament stem cells (PDLSCs) resulted in the inhibition of osteogenic differentiation through disrupting Wnt/β-catenin signaling. However, this inhibition was restored upon administration of recombinant human TRX1 (rhTRX1). Importantly, rhTRX1 treatment decreased ROS generation, activated Wnt/β-catenin signal pathway and considerably promoted the alveolar bone repair of periodontitis mice with diabetes. These findings highlighted the crucial protective role of TRX1 in periodontitis with diabetes and suggested that it may serve as a potential therapeutic target for refractory periodontitis associated with oxidative stress.